The Effect of Rubber Crumbs on Marshall Properties for Warm Mix Asphalt (Journal of Engineering, 2023)
A new pavement technology has been developed in Highway engineering: asphalt pavement production is less susceptible to oxidation and the consequent damages. The warm mix asphalt (WMA) is produced at a temperature of about (10-40) oC lower than the hot asphalt paving. This is done using one of the methods of producing a WMA. Although WMA's performance is rather good, according to previous studies, as it is less susceptible to oxidation, it is possible to modify some of its properties using different materials, including polymers. Waste tires of vehicles are one of the types of polymers because of their flexible properties. The production of HMA, WMA, and WMA modified with proportions of (1, 1.5, and 2%) of rubber crumbs by the dry method are accomplished in this work. Marshall Test and volumetric properties determination are performed to evaluate its performance. The results showed that using 1% of rubber crumbs as a replacement for fine aggregate in the warm asphalt mixture produced the best properties of the WMA compared to the conventional WMA.